A Comparative Analysis Of Interval Cholecystectomy And Early Cholecystectomy Among Patients Of Acute Cholecystitis At A Tertiary Care Centre (Journal of Pharmaceutical Negative Results, 2022)
Background: Comparative evaluation of the efficacy of Interval Cholecystectomy and Early Cholecystectomy Among Patients of AcuteCholecystitis.Materials & methods: A total of 100 patients with presence of acute cholecystitis were analysed. All the patients were broadly andrandomly divided into two study groups as follows: Group A: 50 patients who were schedule to undergo interval cholecystectomy,andGroup B: 50 patients who were schedule to undergo early cholecystectomyComplete history of all the patients was obtained. Allpatients were subjected to detailed history including, chief complaints, history of present and past illness, personal history, familyhistory, treatment and drug history. All the operative procedures were carried out under the hands of skilled and experienced surgeons.Follow-up was done and complications (if any) were recorded separately. All the results were recorded in Microsoft excel sheet andwere analysed by SPSS software.Results: Occurrence of postoperative wound infection and biliary leaks was higher among the patients of group B in comparison topatients of group A.Mean hospital stay among the patients of group A and group B was 5.6 days and 9.1 days respectively. Whilecomparing statistically, significant results were obtained.Conclusion: Interval Cholecystectomy shows better results in comparison to Early Cholecystectomy among patients of AcuteCholecystitis in terms of occurrence of postoperative complications and shorter duration of hospital stay.